(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: : The surgical management of patients presenting with acute calculus cholecystitis remains controversial. Objective: The aim of this study was to evaluate the safety and feasibility of early laparoscopic cholecystectomy for acute calculus cholecystitis and to document the outcome of early laparoscopic cholecystectomy. Methodology: This observational comparative study was carried out in the Department of General Surgery of Sylhet MAG Osmani Medical College Hospital, Sylhet from July 2006 to June 2008, a period of 24 months. The study group enrolled 101 patients of both sexes who underwent laparoscopic cholecystectomy surgery and divided into two groups. 51 patients with a diagnosis of acute calculus cholecystitis were assigned randomly to early laparoscopic cholecystectomy within 72 h of admission (early group, n=51) or to initial conservative treatment followed by elective laparoscopic cholecystectomy, 6 to 12 weeks later (elective group, n=50). Results: There was no significant difference in operation times (early, 81.98 vs elective, 79.96), conversion rates (early, 5.88% vs elective 10%) or postoperative complications (early 31,4% vs elective,24%).However, during early laparoscopic cholecystectomy distended gallbladder containing infected bile was more in 41 patients (80.01%) while 04 patients (09%) and 03 patients (7.20%) in elective laparoscopic cholecystectomy (p>0.05) and significantly (p<0.05) more modification in operative techniques in early group than elective group. In addition, early group had shorte hospital stay (8.37 vs 12.62 days0 and lower treatment cost (5243.13 vs 7327) which were statistically significant (p<0.05). Conclusion: In conclusion laparoscopic cholecystectomy during the early admission with acute calculus cholecystitis can be performed safely and successfully. Earlier surgery has a beneficial impact for patients and the National Health Service. Journal of National Institute of Neurosciences Bangladesh, 2019;5(2): 161-166